2011
DOI: 10.3390/ijerph8020613
|View full text |Cite
|
Sign up to set email alerts
|

Hazardous Compounds in Tobacco Smoke

Abstract: Tobacco smoke is a toxic and carcinogenic mixture of more than 5,000 chemicals. The present article provides a list of 98 hazardous smoke components, based on an extensive literature search for known smoke components and their human health inhalation risks. An electronic database of smoke components containing more than 2,200 entries was generated. Emission levels in mainstream smoke have been found for 542 of the components and a human inhalation risk value for 98 components. As components with potential carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
475
0
18

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 687 publications
(494 citation statements)
references
References 37 publications
1
475
0
18
Order By: Relevance
“…40 Higher urinary cadmium concentrations among men were associated with higher levels of total and free testosterone and estradiol before adjusting for smoking. 41 In addition to potential effects of cadmium on the reproductive system, cigarette smoke contains more than 5000 other chemicals, including several which have been characterized as having adverse effects on reproduction, 42 and these need to be explored further in relation to couples' capacity to conceive.…”
Section: Discussionmentioning
confidence: 99%
“…40 Higher urinary cadmium concentrations among men were associated with higher levels of total and free testosterone and estradiol before adjusting for smoking. 41 In addition to potential effects of cadmium on the reproductive system, cigarette smoke contains more than 5000 other chemicals, including several which have been characterized as having adverse effects on reproduction, 42 and these need to be explored further in relation to couples' capacity to conceive.…”
Section: Discussionmentioning
confidence: 99%
“…[6] Inhalation of such smoke regularly for long time can aggravate the situation and lead to serious health hazards. [7] The mean TC value in smokers was 202.2 ± 26.7 mg/dL, whereas in non-smokers, it was 162.2 ± 22.2 mg/dL (P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco company documents and reports disclosed by litigation (The Legacy Tobacco Documents Library, LTDL; https://industrydocuments.library.ucsf.edu/tobacco/) strengthened public health scientists' suspicions that such a diversity of tobacco additives is incorporated into cigarettes to make them more attractive, palatable and desirable to potential consumers 2,3,5,6,7,8,9,10,11 . By doing so, tobacco additives would facilitate smoking initiation and maintenance thereby increasing prevalence of smoking and tobacco-related diseases in the population.…”
Section: Introductionmentioning
confidence: 99%
“…Menthol is a local pain-relieving agent and it is fair to say that it contributes to "smooth" tobacco smoke 6 . By reviewing the literature on sugars as tobacco additives, Talhout et al 8 concluded that there are consistent indications that sugars mask tobacco smoke harshness and throat impact of tobacco smoke 8,9,10 . Moreover, the authors pointed out that the sweet taste and agreeable smell of caramelized sugars are appreciated in particular by starting adolescent smokers 8 .…”
Section: Introductionmentioning
confidence: 99%